Psoas Muscle Infiltration Masquerading Distant Adenocarcinoma - Kamel A. Gharaibeh; Arnaldo Lopez-Ruiz; Tauqeer Yousuf (Case Reports in Gastrointestinal Medicine)
Malignant metastasis to the psoas muscle is rare. We report a case that clinically mimicked psoas abscess that was subsequently proven to be from metastatic disease secondary to adenocarcinoma of the duodenum. A 62-year-old male presented with a seven-month history of right lower quadrant abdominal pain and progressive dysphagia. CT scan of abdomen-pelvis revealed a right psoas infiltration not amenable to surgical drainage. Patient was treated with two courses of oral antibiotics without improvement. Repeated CT scan showed ill-defined low-density area with inflammatory changes involving the right psoas muscle. Using CT guidance, a fine needle aspiration biopsy of the right psoas was performed that reported metastatic undifferentiated adenocarcinoma. Patient underwent upper endoscopy, which showed a duodenal mass that was biopsied which also reported poorly differentiated adenocarcinoma. In this case, unresponsiveness to medical therapy or lack of improvement in imaging studies warrants consideration of differential diagnosis such as malignancy. Iliopsoas metastases have shown to mimic psoas abscess on their clinical presentation and in imaging studies. To facilitate early diagnosis and improve prognosis, patients who embody strong risk factors and symptoms compatible with underlying malignancies who present with psoas imaging concerning for abscess should have further investigations.